The impact of CO2 emissions and economic growth on energy consumption in 58 countries - Kais Saidi; Sami Hammami (Energy Reports, 2015)
This paper attempts to investigate the impact of economic growth and CO2 emissions on energy consumption for a global panel of 58 countries using dynamic panel data model estimated by means of the Generalized Method of Moments (GMM) for the period 1990-2012. We also estimate this relationship for three regional panels; namely, from Europe and North Asia, Latin America and Caribbean, and Sub-Saharan, North African and Middle Eastern. The empirical evidence indicates significant positive impact of CO2 emissions on energy consumption for four global panels. Economic growth has a positive impact on energy consumption and statistically significant only for the four panel.
Keywords: 330; CO emissions; Economic growth; Energy consumption